RESEARCH: TOWARDS A MULTIDISCIPLINARY APPROACH - Victor AGANBI (IJRDO - Journal of Social Science and Humanities Research, 2020)
Research is a process of discovering the nature and pattern of relationships that exist among diverse phenomena that permits prediction and control. Finding the uniformities underlying these phenomena and integrating them into a defined structure is a tenuous and complicated effort. This is made more complex with the prevalence of mixed tools, types, and methods applicable to different disciplines. Furthermore, researches are increasingly collaborating to conduct cross functional studies singularly or collaboratively. Thus, selecting and adopting a suitable research method for carrying out a given research can frustrate the realization of the aims and objectives of the endeavor. This study examines the nature of this challenge in the researchers’ attempt to understand the various research approaches applicable to different disciplines, identifying the tools, types and methods deployed in various contexts. Research involves integrated processes commencing with the identification of a researchable problem that dovetails into writing of the report. This highlights the doctrinal approach, from the legal disciplines, which places reliance on sources such as research textbooks, journal articles, online materials amongst others. Whereas the Social Science, Arts and Humanities weigh more on survey and statistical analytics in addition to these content analysis and desktop methods. This research explores a mixed bag, pluralist approach. The objective is that the multi-disciplinary approach to research and research writing will become the template for integrated research. This paper concludes that the type of research determines the method, type and ultimately determines the type and method used in the analysis and presentation of data.